EFFECT OF WELDING CURRENT (SMAW) ON TENSILE STRENGTH AND MICROSTRUCTURE OF S45C STEEL - Muhaemin Al Fikri; Iwan Nugraha Gusniar; Viktor Naubnome (TRAKSI, 2022)
Welding is a metal joining technique by partially melting the parent metal and filler metal with or without additional metal and producing a continuous connection. One type of welding that is often used is SMAW (Shieled Metal Arc Welding) welding. In SMAW welding, the influence of the current used plays an important role in welding. Because it affects the results of the strength of the welded joint. This research was conducted to determine the mechanical properties of tensile testing and microstructure under the influence of different currents. In this research, the test material is S45C steel and the current variation is 90 A, 110 A, and 120 A and the type of electrode used is E7016 LB57. The results obtained from the tensile test have the optimum value at 120 A with a tensile strength of 49.43 kg/mm while 110 A with a tensile strength of 43 kg/mm and 90 A with a tensile strength of 11.04 kg/mm. for testing the microstructure seen in the welded parts and the heat affected area. Keywords: variations in welding current, welding smaw, S45C, tensile strength.